Heterosis for seedling characters in cardamom (Elettaria cardamomum Maton) - Ankegowda, K Padmini, M N Venugopal, S J (Journal of Spices and Aromatic Crops, 2000)
A study was conducted to assess the nature and extent of relative heterosis, heterobeltiosis and economic heterosis in cardamom (EZettaria cardamomum) hybrids under nursery conditions. Among the 54 cardamom hybrids evaluated for seedling characters, NKE-9 x NKE-34, NKE-19 x NKE-12, NKE-3 x RR-1 and NKE-34 x NKE-12 were the best for plant height, number of leaves per plant, leaf length and leaf breadth, respectively. No positive and significant economic heterosis was observed in the hybrids for number of leaves per plant. Nine hybrids exhibited significantly higher and positive heterobeltiosis and economic heterosis for all the characters studied except number of leaves per plant.